Mitochondria-derived peptide MOTS-c restores mitochondrial respiration in type 2 diabetic heart - Pham, Toan; Taberner, Andrew; Hickey, Anthony; Han, June-Chiew (Frontiers in Physiology, 2025)
IntroductionType 2 diabetes (T2D) is a global epidemic, and heart failure is the primary cause of premature death among T2D patients. Mitochondrial dysfunction has been linked to decreased contractile performance in diabetic heart, partly due to a disturbance in the mitochondrial capacity to supply adequate metabolic energy to contractile proteins. MOTS-c, a newly discovered mitochondrial-derived peptide, has shown promise as a therapeutic for restoring energy homeostasis and muscle function in metabolic diseases. However, whether MOTS-c therapy improves T2D heart function by increasing mitochondrial bioenergetic function remains unknown.MethodsHere we studied the mitochondrial bioenergetic function of heart tissues isolated from a rat model mimicking type 2 diabetes induced by a high-fat diet and low-dose streptozotocin. Treated diabetic group received MOTS-c (15 mg/kg) daily injection for 3 weeks. We employed high-resolution respirometric and fluorometric techniques to simultaneously assess mitochondrial ATP production and hydrolysis capacity, reactive oxygen species (ROS) production, and oxygen flux in cardiac tissue homogenates.ResultsWe found that untreated T2D rats had hyperglycemia, poor glucose control, and left ventricular hypertrophy relative to controls. T2D mitochondria showed decreased oxygen flux at the oxidative phosphorylation (OXP) while ROS production, ATP production and hydrolysis rates remained unchanged. Diabetic rats treated with MOTS-c showed decreased fasting glucose levels, improved glucose homeostasis, and decreased degree of cardiac hypertrophy. At the subcellular level, MOTS-c treated mitochondria showed increased OXPHOS respiration and ROS levels and decreased ATP hydrolysis rate during anoxic conditions.DiscussionThese findings demonstrate beneficial effects of MOTS-c treatment on glucose homeostasis and suggest a useful therapeutic option for diabetic-related cardiomyopathy and mitochondrial dysfunction.